Activation of NLRP3 signalling accelerates skin wound healing. Issue 1 (2nd November 2017) - Ito, Hiroyasu; Kanbe, Ayumu; Sakai, Hiroyasu; Seishima, Mitsuru
Abstract: The process of skin wound healing involves the following three steps: inflammation, tissue formation and tissue remodelling. These optimal steps are required for the development of normal wound healing. Recent reports demonstrated that inflammasomes are involved in the innate immune response. In the present study, we examined whether the activation of inflammasomes affects the process of skin wound repair. The skin wound repair model was established using wild‐type (WT), NACHT, LRR and PYD domains‐containing protein 3 (NALP3) knockout (KO) and ASC‐KO mice. The wounds were observed every other day, and changes in wound size over time were calculated using photography. Wound repair in NALP3‐KO and ASC‐KO mice was significantly impaired compared with WT mice. Isoliquiritigenin, an inhibitor of NALP3, decreased the rate of wound repair in WT mice. mRNA expression of pro‐inflammatory cytokines in the wound sites of NALP3‐KO mice was markedly decreased compared with WT mice. Treatment with adenosine triphosphate (ATP), a ligand of NALP3, upregulated the mRNA expression of pro‐inflammatory cytokines at the wound site and accelerated wound healing in the WT mice. Scratch assay revealed that ATP accelerated wound closure in mouse embryonic fibroblasts from WT mice but not from NALP3‐KO mice. In conclusion, the present study demonstrated that NALP3 pathway activation is involved in wound repair, and the topical use of ATP may be useful as an effective treatment for accelerating wound healing.